2009
DOI: 10.1080/02713680802676885
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Selenite-Induced Cataractogenesis by N-Acetylcysteine in Rats

Abstract: N-acetylcysteine appears to inhibit selenite-induced cataractogenesis in the rat model, and this seems to be caused by the prevention of oxidative damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…GSH protects the lens from oxidative damage and also maintains the functions and transparency of the lens by protecting the protein sulfhydryl groups from oxidation. In addition, GSH has been found to decrease concomitantly with seleniteinduced cataractogenesis [19][20][21][22][23][24][25]36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GSH protects the lens from oxidative damage and also maintains the functions and transparency of the lens by protecting the protein sulfhydryl groups from oxidation. In addition, GSH has been found to decrease concomitantly with seleniteinduced cataractogenesis [19][20][21][22][23][24][25]36].…”
Section: Discussionmentioning
confidence: 99%
“…The reliability and extensive characterization of selenite cataract makes it a useful rodent model for rapid screening of potential anticataract agents [16]. Molecules that have been shown by experimental studies to prevent selenite-induced cataractogenesis include melatonin [15], resveratrol [17], acetyl-L-carnitine [18,19], ellagic acid [20], soya bean [21], L-cysteine [22], N-acetylcysteine [23], an extract of Pleurotus ostreatus [24], and onion juice [25]. However, there is a need to evaluate additional compounds for their anticataractogenic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested that intake of antioxidant-rich foods may slow the progression of cataract. Therefore, to date, a number of antioxidant chemicals and drugs such as L-carnitine, acetyl-L-carnitine, lycopene, melatonin, resveratrol, α-lipoic acid, Ginkgo biloba, α-tocopherol, N-acetylcysteine, pyruvate and verapamil have been used to prevent experimental cataract in the lens (11,12,14,15,(18)(19)(20)(21)(22)(23)(24)(25). They were found to be effective in preventing cataract, but none have been implemented in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Several compounds with antioxidant properties have been reported to prevent selenite-induced cataracts, such as resveratrol [12], saffron [13], ellagic acid [14], garlic [15], melatonin [16], drevogenin D [17], caffeine [18], ebselen [19], lycopene in vivo [20], N-acetyl-L-carnitine in vitro and in vivo [2123], and Ocimum sanctum in vivo and ex vivo [24]. In fact, N-acetylcysteine (NAC), a glutathione (GSH) prodrug, has previously been tried in selenite-induced cataracts in vivo [25] and was shown to prevent oxidative damage to the lens, slowing down cataractogenesis.…”
Section: Introductionmentioning
confidence: 99%